Early Clinical Failure of a Cementless Thumb Basal Joint Hemiarthroplasty for the Treatment of Trapeziometacarpal Osteoarthritis - Peter J. Evans, MD, PhD, FRCSC, FAAOS; Patrick G. Marinello, MD; Mark Shreve, MD (JBJS Open Access)
Background:. The purpose of our study was to evaluate the clinical results and survivorship of a metal-stemmed implant for thumb basal joint hemiarthroplasty. Methods:. We performed 35 basal joint hemiarthroplasties in 32 patients. Of these, 26 thumbs (25 patients) had clinical follow-up of at least 12 months at our first review in 2014. The mean age of the patients was 54 years (range 43-68 years), and 88% were females. All patients had Eaton-Littler Stage II or III arthritis preoperatively. Average follow-up was 22.5 months (range 12-41 months) for the initial review and 144.4 months (range 126-160 months) for the last chart review and phone follow-up. The main outcomes were revision rate and time to revision. Preoperative and postoperative radiographs were examined to determine the amount of overall thumb ray lengthening and amount of subsidence of the implant between those revised and unrevised. Results:. At 12-month follow-up, 16 of 26 thumbs (61.5%) had been revised with implant removal, resection of the remaining trapezium, and ligament reconstruction with tendon interposition. Another 3 thumbs were symptomatic and planning on future revision. Continued pain, stem loosening, and implant subsidence into the trapezium were the clinical reasons for revision. The mean time to revision was 18.1 months (range 8-41 months). Conclusions:. We found poor implant survivorship and an unacceptably high rate of reoperation with the stemmed thumb basal joint hemiarthroplasty device in our patient cohort. Level of Evidence:. Therapeutic Study–Level IV Case Series. See Instructions for Authors for a complete description of levels of evidence.